An experimental investigation on the evaporation of polystyrene encapsulated phase change composite material based nanofluids. (5th March 2020) - Muthya Goud, V.; Vaisakh, V.; Joseph, Mathew; Sajith, V.
Graphical abstract: Highlights: Synthesis of nanoencapsulated phase change composite material by mini emulsion polymerization. Excellent stability for PCM based nanofluids. 35% reduction in surface tension for PCM based nanofluid as compared to deionized water. 70% lower evaporation rate for PCM nanofluid as compared to water, in stagnant condition. 32% lower evaporation rate for PCM nanofluid as compared to water, in flow condition. Abstract: The use of phase change material (PCM) based nano fluids is an attractive option for the thermal management of power plants. The objective of the present study is to investigate the evaporation characteristics of PCM based nanofluid. PCM nanofluid was prepared by dispersing nano encapsulated phase change material (nEPCM) in deionized water. The composite PCM was synthesized by mixing paraffin wax with petroleum jelly in the ratio 10:90. The nEPCM was synthesized by mini-emulsion polymerization process in which PCM is encapsulated with in polystyrene shell. The characterization of synthesized nEPCM was done by Differential scanning calorimetry, Scanning electron microscope and Dynamic light scattering. The thermophysical properties of PCM nanofluid were estimated using standard apparatus. Experiments were performed to estimate evaporation rate of different concentrations of PCM nanofluid with humidity and temperature, both in stagnant and forced circulation conditions. PCM nanofluid showed 70% and 37% lower evaporation rate than water, in stagnant and forced circulation conditions, respectively. The evaporation rate of PCM nanofluid was found to increase with increase in temperature and concentration. The lower evaporation loss of PCM based nanofluids results in reduced consumption of makeup water in thermal power plants.